Value creation in listed companies: A bibliometric approach - Lafont, Juan; Ruiz, Felipe; Gil-Gómez, Hermenegildo; Oltra-Badenes, Raul (Journal of business research, 2020)
This paper presents a quantitative overview of the research field of value creation for listed companies. The study is based on bibliometric analysis of articles published in the main database of the Web of Science between 1900 and 2018. In total, 213 articles were identified and quantitatively analyzed. The study shows that despite recent emergence and limited background regarding number of publications and citations, this topic is attracting interest as a scientific research field. It therefore has a promising future as a subject of research. The interest in this subject by countries, authors, and institutions is primarily from the People’s Republic of China, ahead of Western countries such as the United States and the UK. However, the fledgling status of this subject as a research topic and its recent growth suggest that researchers and institutions in many countries will focus their efforts on increasing and expanding research in this area.